Are Lean Manufacturing and Corporate Social Responsibility Conflicting or Complimentary Strategies? - Pearson, Paul Michael (2006)
Increasingly within both manufacturing and service sectors companies are adopting Lean principles and philosophies as a way of reducing costs and gaining competitive advantage in an ever increasing global market environment. At the same time there is an increase in awareness of Corporate Social Responsibility, both in terms of instigation and reporting (Sarbannes Oxley) either through increasing shareholder pressure or transparency.